Islamische Philosophie und die Krise der Moderne : Das Verhältnis von Leo Strauss zu Alfarabi, Avicenna und Averroes - Tamer, Georges (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This book fills the gap in the research of Leo Strauss (1899 - 1973) showing the influence of Alfarabi (870 - 950), Avicenna (980 - 1037) and Averroes (1126 - 1198) on his thought. The first part is historically-philologically oriented and contains neglected material where it presents a new approach to Leo Strauss's work. The second part discusses Strauss's reaction towards the crisis of modernity, stimulated by Islamic philosophy, as well as his nomic understanding of religion as the essential features of his political philosophy. Since Alfarabi is the Muslim Philosopher who had the greatest influence on Strauss's thought, his philosophy will also be analysed. This book offers the opportunity to discover an interesting aspect of the encounter of cultures, and contribute to a modern reception of Islamic philosophy.